EKSPLORASI PEMBELAJARAN MENYIMAK BERBASIS TEKNOLOGI PADA SISWA KELAS IV DI SDN 64/I MUARA BULIAN - Kurniyati, Wiwik; Natasya T; Nahara, Afifa Suci; Ginting, Femi BR; Khoirunnisa; Silvina Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe technology-based listening learning among fourth-grade students at SDN 64/I Muara Bulian, covering the implementation process, students' experiences, challenges, and supporting factors. A qualitative descriptive approach with a case study design was employed. Data were collected through observation, interviews, and documentation, analyzed using Miles and Huberman's interactive model, and validated through source and technique triangulation. The findings indicate that learning was conducted in a structured manner using audio-visual and interactive media. Students demonstrated high enthusiasm and active engagement, although both technical and non-technical challenges were identified. Learning success was supported by the appeal of the media, the teacher's facilitative role, and a conducive classroom environment. This study affirms that the integration of technology in listening learning has the potential to create more active and meaningful learning experiences for elementary school students.